Monetary Policy and Fiscal Policy for Economic Development in Indonesia - Suyatna, Nano (Journal of Economicate Studies, 2021)
The Covid-19 pandemic is an extraordinary disaster, affecting all sectors and aspects of life globally. It needs government intervention, because it causes a significant increase in opposition to the economic development that is currently being built in Indonesia. The research method used a descriptive approach which was sourced from quantitative secondary data. The results show that there is an effect of monetary policy and fiscal policy on economic development in Indonesia, with the monetary and fiscal stimuli issued by the government. With this stimulus, it was able to boost unemployment and poverty levels so that they did not continue to increase. Monetary policy and fiscal policy are tools for economic development in order to maintain national economic stability and achieve the welfare of the Indonesian people.